Safety evaluation of the food enzyme tannase from the non‐genetically modified Aspergillus sp. strain TAN 206 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal, 2025)
Abstract The food enzyme tannase (tannin acylhydrolase; EC 3.1.1.20) is produced with the non‐genetically modified Aspergillus sp. strain TAN 206 by Shin Nihon Chemical Co., Ltd. The food enzyme is free from viable cells of the production organism. It is intended to be used in two food manufacturing processes. Dietary exposure was estimated to be up to 0.310 mg total organic solids (TOS)/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 770 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 2484. A search for the homology of the amino acid sequence of the tannase to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions upon dietary exposure to the food enzyme cannot be excluded, but that the likelihood is low. Based on the data provided, the Panel concludes that this food enzyme does not give rise to safety concerns under the intended conditions of use.